Intrinsic metabolic and immune impairments in a genetic mouse model of schizophrenia - Martina Belmonte; Sofia Lopez Cardoso; Anabella A. Di Pietro; Florencia Veigas; Laura A. Pasquini; Diego M. Gelman (Schizophrenia)
Abstract Schizophrenia is a disorder of still unknown aetiology characterized by positive, negative and cognitive symptoms. The first evident signs emerge at the end of adolescence and the beginning of adulthood as a psychotic episode. Patients are then treated with antipsychotics to ameliorate positive symptoms. However, this pharmacological approach is ineffective for negative and cognitive ones. Schizophrenia patients also exhibit metabolic and immune alterations, regardless of antipsychotic treatment. Clinical research in this field is challenging, as there is no way to identify people at risk before the first psychotic episode, and once it emerges, antipsychotic treatment is applied, worsening metabolic and immune profiles which may be detrimental for cognitive and negative symptoms. A faithful animal model of schizophrenia may be valuable to understand molecular events and brain regions involved in each of the symptoms, evaluate novel pharmacological compounds for unattended symptoms and explore objective diagnostic strategies. Here, we show that the selective dopamine D2 receptor deletion from parvalbumin interneurons, a mutation that results in schizophrenia-like phenotypes, causes intrinsic metabolic and immune defects in mice, in a similar way to what is described in schizophrenia patients. Mutant animals show dysglycaemia and dyslipidaemia, abnormal white blood cell counts, increased neutrophil-to-lymphocyte ratio, CD4/CD8 ratio imbalances, increased circulating C-reactive protein levels and reactive microglia. Therefore, selective dopamine D2 receptor deletion causes a wide spectrum of phenotypes resembling those described in patients. This animal line may be a useful research tool to expand our knowledge on the aetiology of schizophrenia.